Effect of harvest interval on yield and chemical composition of cassava and effects of foliage from cassava and erythrina subumbrans as supplements to elephant grass and banana leaves for growth of goats : - Vivasane, Souksakhone (Can Tho University, 2017)
To investigate productivity and nutritive value of cassava foliage by harvesting frequency. To estimate sources of basal diets (banana leaves and elephant grass) and of supplements (cassava and Erythrina foliage) on growth of goat.